Evaluation of preventable causes and risk factors of maternal mortality - Bhatia, Ruby; Mohi, Manjit Kaur; Singh, Neeraj (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The primary objective was to evaluate preventable causes of maternal deaths at tertiary, second and primary care in Patiala district, Punjab. Secondary objective was to determine impact of socio-demographic characteristics, anemia and three delays on maternal death. Methods: This is a retrospective observational study carried out between 1. 7. 2013 till 30. 6. 2014, for period of one year in department of a tertiary care hospital and district health authorities catering to secondary and primary care deaths for evaluation of preventable causes and risk factors for maternal deaths at tertiary, secondary and primary level. Results: A total of 54 maternal deaths with MMR of 170.42/100000 live births, occurred in stipulated period, 87.03% at tertiary care, one at second care, 7.41% at home and 3.7% on the way to tertiary care. Majority of maternal deaths (92.6%) were unbooked, between 21-30 years (64.82%) of age, primi or second gravida (35.18%), para 1 or 2 (37.03%), illiterate (40.74%), low income group (57.41%) with rural background (59.26%). Majority of maternal deaths (77.7%) occurred in postpartum period. Most of maternal deaths (75.93%) were due to direct causes, pre-eclampsia 25.93% followed by sepsis (22.2%) and haemorrhage (20.3%). Anemia was contributory factor in 79.63% maternal deaths. 7.4% maternal deaths occurred at home with delay in seeking care while 29.62% died due to delay in reaching care. In 40.42% maternal deaths, it took more than two hours to reach tertiary care hospital. Conclusions: Skilled antenatal, intranatal and postnatal care, women empowerment, counseling, early diagnosis and referral of pre-eclampsia and other high-risk cases with curbing anemia at grass root level is need of millennium. Preventing delay in seeking care or reaching care-a step towards sustainable development goals (SDG) to reduce MMR.